Successive Intercropping of Potato and Mungbean with Sugarcane (The Agriculturists, 2017)
The experiment was carried out at the Bangladesh Sugarcane Research Institute (BSRI) farm at Ishurdi, Pabna, Bangladesh during2008-2009 and 2009-2010to investigate the growth and yield of main crop sugarcane, and companion crops potato and mungbean as successive intercrops. Row to row spacing (RRS) of sugarcane were 80 (S1), 100 (S2) and 120 cm (S3) and sugarcane was intercropped with 1, 2 and 3 rows of potato as 1st intercrop and followed by mungbean with same row ratio as 2nd intercrop. Sugarcane and companion crops potato and mungbean were cultivated following the cultivation methods of BSRI and Bangladesh Agricultural Research Institute (BARI), respectively. To provide more light to intercrops bended leaves of sugarcane on both sides of rows were cut at middle and compared with non-cutting of leaves in respect of growth and yield of main crop and intercrops as well. The total dry matter production, cane yield and sugar yield were the highest at 120 cm RRS of sugarcane (non-leaf cutting=C0) intercropped with 3 rows of potato followed by 3 rows of mungbean (S3C0). The number of tiller and millable canes, and leaf area index (LAI) were the highest at 80 cm RRS of sugarcane (C0) with one row of potato and one row of mungbean (S1C0). The effect of light interception on growth and yield of first intercrop (potato) was insignificant whereas it was significant for second intercrop. Yield of mungbean (2nd intercrop) and light interception ratio (%) was the lowest in S3C1 where sugarcane RRS was 120 cm + 3 R potato followed by 3 R mungbean with leaf cutting (LC). The results of the experiment indicated that sugarcane transplanted at RRS of 120 cm with 3 rows of potato followed by 3 rows of mungbean can be grown as intercrops for increased yield of sugarcane as well as for increased cropping intensity and might be recommended for farmers practice in High Ganges River Flood Plain soils under AEZ 11 of Bangladesh. The Agriculturists 2016; 14(2) 67-76